Impact of repeated four-monthly anthelmintic treatment on Plasmodium infection in preschool children: A double-blind placebo-controlled randomized trial - Kirwan, Patrick; Jackson, Andrew L; Asaolu, Samuel O; Molloy, Sile F; Abiona, Titilayo C; Bruce, Marian C; Cartwright, Lisa Ranford; Neill, Sandra M O’; Holland, Celia V (Kirwan et al. BMC Infectious Diseases, 2020)
BMC Infectious Diseases ,NO.10,PG.1-11